Antioxidant, anticholinesterase activities and polyphenolic constituents of cones of algerian fir (Abies numidica) by LC-ESI-MS/MS with chemometric approach - Mokaddem-Daroui, Habiba; Mostefa, Maya Belhadj; Aydogmus-Ozturk, Fatma; Erol, EBRU; EROL, EBRU; Ozturk, Mehmet; Ertas, Abdulselam; Duru, Mehmet Emin; Kabouche, Ahmed; Kabouche, Zahia (My University, 2021)
The fractions (Fr.1-5) of the hydromethanolic extract of Abies numidica cones were studied for their polyphenol constituents, antioxidant, and anticholinesterase activities. The beta-carotene-linoleic acid, cupric reducing power (CUPRAC), DPPH scavenging, and ABTS radical scavenging assays were used to determine antioxidant activity. Fr.3 exhibited the highest antioxidant activity in ABTS test (IC50: 1.29 mu g/mL), b-carotene-linoleic acid test (IC50: 18.6 mu g/mL) and CUPRAC (A(0.5): 33.8 mu g/mL) assays. Three fractions (Fr.2-4) promising antioxidant activity were analyzed using LC-MS/MS for their phenolic compositions. Taxifolin (155.9-2816.2 mu g analyte/g extract), hyperoside (353.0-2045.5 mu g/g), vanillin (1488.9-1529.9 mu g/g), tannic acid (1281.6-1416.8 mu g/g), rosmarinic acid (1063.1-1149.3 mu g/g), coumarin (683.0-772.6 mu g/g), quercetin (881.0 mu g/g), and catechin (277.7-400.2 mu g/g) were identified in the antioxidant fractions. Moreover, the anticholinesterase activity was also performed using the in vitro spectroscopic Ellman method. The antioxidant fractions exhibited moderate butyrylcholinesterase inhibitory activity. The multi-ware analysis was performed to understand the origin of bioactivities. According to principal component analysis, it is detected that the hyperoside, catechin, taxifolin, and tannic acid were responsible for the antioxidant activity. Therefore, the cones of Abies numidica can be considered as potent antioxidant and anticholinesterase sources in food and pharmaceutical industries, commercially.